Rancangan Usulan Peningkatan Output Produksi dan Pengendalian Produksi di PT. X - Alexander James Mokaliran; Tanti Octavia (Jurnal Titra, 2023)
PT. X is one of roof trusses manufacturer in Indonesia. Due to intense competition between competitors, company needs to provide good service to customers. The problem that happened is the the company’s production capacity per shift still hasn’t been able to meet customer demands, therefore the company often does overtime on production. Inventory cost also being the problem in company where the raw materials are more than demand it cause more inventory cost. The purpose of this study is to allocated the workload with consider the production capacity and find out the best option for controlling raw material inventory. Production capacity can be calculated from standard time and then workload allocation to minimize overtime and idle time. Workload allocation can reduce overtime by 90,8% and idle time by 47,7%. Continuous review system, periodic review system, and multi-item joint order methods will be used as raw material ordering methods. These methods will be compared with the current conditions based on total inventory cost. In conclusion, continuous review system method has the smallest total inventory cost compared to other methods and the current conditions of the company that reduce the cost by 3,55%.